Mycetoma caused by Microascus gracilis: a novel agent of human eumycetoma in Sudan. (30th January 2021) - Mhmoud, Najwa A; Siddig, Emmanuel Edwar; Nyuykonge, Bertrand; Bakhiet, Sahar Mubarak; van de Sande, Wendy W J; Fahal, Ahmed Hassan
Abstract: Species of the genus Microascus are uncommon agents of human diseases despite their ubiquitous presence in the environment. In this communication, the first case of white grain eumycetoma caused by the fungus Microascus gracilis is reported. The patient was initially misdiagnosed as having actinomycetoma based on the grains morphological and cytological features and was treated with antimicrobial therapy with no clinical improvement. She underwent wide local surgical excision to improve the response to medical treatment and further grain cultural, molecular and taxonomy techniques were conducted and the diagnosis of mycetoma due to M. gracilis was established. The antifungal susceptibilities of this isolate to nine drugs were tested in vitro and they showed poor activity. Combination therapy with surgery and itraconazole led to complete recovery. A medical literature search revealed no previous report on M. gracilis as a causative agent of eumycetoma and hence we are reporting this new causative agent of human eumycetoma. Also, the difficulty in the management of this patient emphasizes the need for accurate and appropriate diagnostic tests for the identification of mycetoma-causative organisms and thus proper management.